2018
DOI: 10.1186/s12199-018-0693-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-intensity bodyweight training with slow movement on motor function in frail elderly patients: a prospective observational study

Abstract: BackgroundSlow-motion training, an exercise marked by extremely slow movements, yields a training effect like that of a highly intense training, even when the applied load is small. This study evaluated the effects of low-intensity bodyweight training with slow movement on motor function in frail, elderly patients.MethodsNinety-seven elderly men and women aged 65 years or older, whose level of nursing care was classified as either support required (1 and 2) or long-term care required (care level 1 and 2), volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…We developed a slow-motion weight training program using one’s own body weight that can be easily performed by frail elderly subjects at home. In a previous study, it was confirmed that walking function and lower limb muscle strength were improved by slow training using one’s own body weight for 3 months [5]. In this study, exercise training was performed by elderly individuals for 12 months, and whether long-term improvements were achieved was examined.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We developed a slow-motion weight training program using one’s own body weight that can be easily performed by frail elderly subjects at home. In a previous study, it was confirmed that walking function and lower limb muscle strength were improved by slow training using one’s own body weight for 3 months [5]. In this study, exercise training was performed by elderly individuals for 12 months, and whether long-term improvements were achieved was examined.…”
Section: Introductionmentioning
confidence: 80%
“…We developed an LST program based on a previous program [5]; for 12 months, participants underwent the exercise interventions once or twice per week, depending on the individual’s required level of nursing care. Regarding the amount of physical exercise, two sets of six different types of exercise (to strengthen the thighs, lower legs, buttocks, abdomen, chest, and back) were performed at a pace of eight times per minute (all exercises were performed with a hold time of 1–2 s with a rest period of 1–2 s); the sets of exercises were separated by 1-min breaks.…”
Section: Methodsmentioning
confidence: 99%
“…This may account for the improvements on the TUGT and FTSST found in this study. Previously, studies by Kanda et al (2018) and Watanabe et al (2014) showed significant increases in physical performance ability and muscle strength using low-intensity bodyweight and low-intensity (30% of one repetition maximum) resistance training, respectively. This is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 98%
“…In other words, toe grip training alone is not sufficient to improve locomotive performance in nursing home residents [16, 17]. Toe grip training needs to be combined with a conventional aerobic or resistance training program [33]. Toe grip training is a safe and convenient training method that can be performed at any time (for example, while watching TV) and anywhere (for example, in the bed or bath).…”
Section: Discussionmentioning
confidence: 99%